Mentalizing Bodies: Explicit Mentalizing Without Words in Psychotherapy - Jensen, Thomas Wiben; Høgenhaug, Stine Steen; Kjølbye, Morten; Bloch, Marie Skaalum (Frontiers in Psychology, 2021)
Introduction: Mentalization concerns the human ability to understand the actions of others (and ourselves) in terms of intentional mental states. Often the notion is understood and described via the poles of automatic, non-verbal implicit mentalization as opposed to conscious, verbal explicit mentalization. In this article we challenge this standard division by examining examples from psychotherapy while arguing that explicit mentalization can also be carried out via embodied non-verbal actions. Method: Four cases of real-life interaction from psychotherapy sessions are analysed from the perspective of multimodal interaction analysis and re-enactment. The analyses are based on video data transformed into transcriptions and anonymized drawings from a larger cognitive ethnography study conducted at a psychiatric Hospital in Denmark. On a theoretical level the analyses are informed b a more intersubjective perspective on mentalization in combination with new insights from embodied cognition. Results: The analyses demonstrate the gradual development from predominantly implicit mentalizing to predominantly explicit mentalizing. In the latter part of the examples the mentalizing activity is initiated by the therapist on an embodied level, but in an enlarged and complex manner indicating a higher level of awareness, imagination and reflection. Thus, the standard assumption of explicit mentalization as contingent on verbal language is challenged since it is demonstrated how processes of explicit mentalization can also take place on an embodied level without the use of words. Conclusion: This article presents a model for investigating the processes of implicit and explicit mentalization as a gradual phenomenon interwoven with embodied dynamics in real life interaction. Thus, the analyses establish a window into how mentalization is in fact carried out by psychotherapists through interaction that testifies to the importance of embodied non-verbal behavior in psychotherapy. Further, informed by the notion of affordance-space the study, on a more general level, points to alternative ways of thinking about the role of our bodies and the environment in conveying more complex understandings of other people.